2021
DOI: 10.1016/j.clim.2021.108699
|View full text |Cite
|
Sign up to set email alerts
|

The role of A-to-I RNA editing in infections by RNA viruses: Possible implications for SARS-CoV-2 infection

Abstract: RNA editing is a fundamental biological process with 2 major forms, namely adenosine-to-inosine (A-to-I, recognized as A-to-G) and cytosine-to-uracil (C-to-U) deamination, mediated by ADAR and APOBEC enzyme families, respectively. A-to-I RNA editing has been shown to directly affect the genome/transcriptome of RNA viruses with significant repercussions for viral protein synthesis, proliferation and infectivity, while it also affects recognition of double-stranded RNAs by cytosolic receptors controlling the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 59 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…The role of APOBEC and ADAR proteins in host innate immunity and their viral directed activities raises the possibility of host immunity contributing to the intra-host heterogeneity observed in the SARS-CoV-2 genome (22,(24)(25)(26). Indeed, this has been proposed as the underlying mechanism for the D614G mutation (27). Whether the observed frequent mutation and back mutation events at position 142 reported here are due to RNA editing is of interest and requires analysis beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 84%
“…The role of APOBEC and ADAR proteins in host innate immunity and their viral directed activities raises the possibility of host immunity contributing to the intra-host heterogeneity observed in the SARS-CoV-2 genome (22,(24)(25)(26). Indeed, this has been proposed as the underlying mechanism for the D614G mutation (27). Whether the observed frequent mutation and back mutation events at position 142 reported here are due to RNA editing is of interest and requires analysis beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, prediction of interaction between SARS-CoV-2 genome and human proteome indicated that highly structured region at the 5′ end had the large number of interactions with proteins such as 1) ATP-dependent RNA helicase - DDX1, that was previously reported to be essential for Avian infectious bronchitis coronavirus replication [35] and 2) ADAR double-stranded RNA-specific editases, that catalyse the hydrolytic deamination of adenosine to inosine, result in affecting viral protein synthesis, proliferation and infectivity [36], and 3) 2′-5′-oligoadenylate synthetases that control viral RNA degradation [20], [37], [38]. Some of these proteins could interact with a leader sequence of sgRNA.…”
Section: Resultsmentioning
confidence: 99%
“…SL3 is conserved only in subgroups of beta and gammaCoVs [4] and contains TRS-L sequences that take part in discontinuous transcription [11,44]. Recently, a prediction of interaction between the SARS-CoV-2 genome and the human proteome indicated that a highly structured region at the 5′ end had a large number of interactions with proteins such as (1) ATP-dependent RNA helicase-DDX1, which was previously reported to be essential for Avian infectious bronchitis coronavirus replication [18,47], (2) adenosine deaminases acting on RNA (ADAR) that catalyzes the hydrolytic Recently, a prediction of interaction between the SARS-CoV-2 genome and the human proteome indicated that a highly structured region at the 5 end had a large number of interactions with proteins such as (1) ATP-dependent RNA helicase-DDX1, which was previously reported to be essential for Avian infectious bronchitis coronavirus replication [18,47], (2) adenosine deaminases acting on RNA (ADAR) that catalyzes the hydrolytic deamination of adenosine to inosine, which affects viral protein synthesis, proliferation and infectivity [18,48], and (3) 2 -5 -oligoadenylate synthetases which control viral RNA degradation [18,49,50]. Some of these proteins could interact with a leader sequence of sgRNA.…”
Section: Model Of Secondary Structure For Sgrna Mmentioning
confidence: 99%